Green mobility at home, green mobility at tourism destinations: A cross-country study of transport modal choices of educated young adults. (July 2022) - Zamparini, L.; Domènech, A.; Miravet, D.; Gutiérrez, A.
Abstract: Fostering environmentally friendly transport solutions for visitors lies at the core of the strategies aimed at implementing sustainable tourism destinations. In this sense, this study aims to identify the determinants of green mobility choices taken by young adults during their holidays. It is based on a survey proposed to Italian and Spanish University students. The study demonstrates the intrinsic relationship between the transport mode choices at home and at tourism destinations. The correlation of other variables that could cause bias on mobility choices at tourism destinations is tested (visits undertaken, and transport mode used to reach the destination). The use of bivariate probit models allows to disentangle that male gender, coastal destinations, and car ownership lead to more unsustainable mobility at tourism destination. In contrast, the results indicate that students visiting top international destinations are more likely to present a greener mobility. Highlights: Determinants of educated young tourists' green mobility at destination are identified. Transport mode choice at home conditions transport mode choices at holidays. En-route holidays are associated with less sustainable transport mode choices. Young adults visiting top international destinations present greener behaviour.